Zhiznennaya istoriya i sportivnaya kar'era olimpiitsa: Osnovnye polozheniya mezhdunarodnogo issledovatel'skogo proekta i rezul'taty pilotazhnogo issledovaniya v Sidnee - Milstein, O. A. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The modern Olympic sport is the independent sphere of activities. It is based on the universal and on it's own values and it forms the rather specific image of an athlete's life, his vital style. The one of the major characteristics of an image of an athlete's life in general and of the olympian in particular is the sports career. The olympian is the basic figure in the Olympic movement, the Olympic family, the Olympic history. How to develop the destinies of olympians, what is their vital way, their vital history as up to this day, in that time, and especially after the end of their sports career? The international historical-sociological research "The vital history and sports career of olympians", both finished sports career and working is called to answer these and many other questions. This trial research has allowed to be convinced of correctness and urgency of the put forward the idea about the realization of the offered project, purposes and tasks, put before it, chosen methods of research and ways of its organization. The results of the trial research were considered at the session of athletes' commission in December 8th, 2000. The unanimous decision to begin the realization of this international project had been accepted.